Harapan Masyarakat Terhadap Peran Anggota Legislatif Perempuan (ALP) Dalam Mendorong Pembangunan Yang Berpihak Pada Perempuan Dan Kemiskinan Di Polman - Syamsu Alam (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
This research is based on the idea that women's representation is the support of society, especially women, to fulfill basic rights and basic rights so that problems related to poverty and other problems of gender inequality can be overcome through the voice of women of parliament. This research uses qualitative approach with descriptive type. The location of the research and the determination of informants was chosen purposively by considering the focus on women. Those selected are those directly involved in the management of development at the village / kelurahan level. The result of the research shows that the general knowledge about the Profile of Women Legislative Members (ALP) in Polman Regency is not satisfactory, their knowledge about ALP profile is not deep because most of them do not know well about other data related to ALP like position and party as well the area of the electoral district of the ALP. This is because the ALP is rarely in direct contact with the community and the media is not utilized. Public expectations of a gender-responsive Development Program Arrangement and ensuring the alignment of Women and the Poor are; The ALP should play an active role in promoting village development programs that must be guarded by involving women and the poor to all stakeholders. The ALP should also encourage existing Regulations / Regulations related to Musrembang Village / Sub District / Regency that ensure the representation of Women, and other Marginal Groups.